Family Institutions and the Global Fertility Transition - Paula Gobbi; Anne Hannusch; Pauline Rossi (Institute of Labor Economics (IZA), 2025)
Much of the observed cross-country variation in fertility aligns with the predictions of classic theories of the fertility transition: countries with higher levels of human capital, higher GDP per capita, or lower mortality rates tend to exhibit lower fertility. However, when examining changes within countries over the past 60 years, larger fertility declines are only weakly associated with greater improvements in human capital, per capita GDP, or survival rates. To understand why, we focus on the role of family institutions, particularly marriage and inheritance customs. We argue that, together with the diffusion of cultural norms, they help explain variations in the timing, speed and magnitude of the fertility decline. We propose a stylized model integrating economic, health, institutional and cultural factors to study how these factors interact to shape fertility transition paths. We find that family institutions can mediate the effect of economic development by constraining fertility responses.
Keywords: J1; 330; fertility; family institutions; marriage; inheritance